Impact of System of Rice Intensification (SRI) Organic Rice on Farmer Welfare in Kolaka District, Southeast Sulawesi, Indonesia - Fyka, Samsul Alam; Limi, Muhammad Aswar; Cristi, Brtiney (Universitas Panji Sakti, 2025)
This research looks at how the System of Rice Intensification (SRI) organic rice growing system affects the well-being of farmers in Baula District, Kolaka Regency. The study looks at income, productivity, production costs, and farmers' views on stakeholder support in order to fill in the gaps in the scant empirical evidence on the socio-economic advantages of SRI-organic practices in Indonesia. We used a quantitative technique using a survey method and comparative descriptive analysis with 56 respondents who were chosen for a specific reason (28 organic SRI farmers and 28 conventional farmers). Farm income computation, the Independent Sample T-Test, and the Likert-scale-based perception analysis were some of the analytical methods used. The results showed that organic SRI farmers earned an average income of Rp125,195,859.00 ha⁻¹ season⁻¹, significantly higher than inorganic farmers (Rp25,874,641 ha season-1). Organic SRI land productivity was recorded at 7,493.16 kg ha-1, more efficient than the inorganic system (6,106.58 kg/ha). Although the production cost of SRI is higher, the economic value is still more profitable due to the higher selling price of organic grain and input efficiency. Farmers' perception of the role of stakeholders is also classified as